2020
DOI: 10.2147/jpr.s273475
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of Intravenous Immunoglobulin for Management of Neuropathic Pain: A Narrative Review</p>

Abstract: Administrations of intravenous immunoglobulin (IVIG), an immune-modulating blood-derived product, may be beneficial for managing neuropathic pain. Here, we review previous studies to investigate the effectiveness of IVIG in managing neuropathic pain due to various neurological disorders. The electronic databases PubMed, Scopus, Embase, and the Cochrane Library were searched for studies published up to February 2020. Two reviewers independently assessed the studies using strict inclusion criteria. Ten studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Chronic pain is associated with neuroinflammation. 28 Several lines of evidence suggest that the mechanical allodynia induced by SNI is secondary to a neuroinflammatory response in the CNS, that is characterized by aberrant microglial activation in the spinal cord. 29 , 30 Gordh et al also reported that patients with severe peripheral neuropathic pain demonstrated upregulation of several chemokines in their cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain is associated with neuroinflammation. 28 Several lines of evidence suggest that the mechanical allodynia induced by SNI is secondary to a neuroinflammatory response in the CNS, that is characterized by aberrant microglial activation in the spinal cord. 29 , 30 Gordh et al also reported that patients with severe peripheral neuropathic pain demonstrated upregulation of several chemokines in their cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Human intravenous immunoglobulin (IVIg) are therapeutic polyspecific IgGs derived from plasma pools of thousands of healthy donors, characterized by multiple immunomodulatory and anti-inflammatory properties. IVIg are used to manage neuropathic pain from various neurological disorders [ 32 ]. While their effectiveness has been demonstrated in several animal models of autoimmune and inflammatory neuropathies [ 33 , 34 ] mimicking Guillain-Barrè syndrome or chronic inflammatory demyelinating polyneuropathy [ 35 ] and also in experimental bortezomib-induced peripheral neuropathy [ 36 ], their use in PIPN has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has revealed that IVIG may be beneficial for managing neuropathic pain. [ 29 ] Some research has reported that IVIG and plasma exchange therapy could effectively improve pain symptoms in some CRPS patients. [ 30 ] Fc γ RI, which is the high‐affinity Fc‐gamma receptor, can bind both IgG‐IC and monomeric IgG.…”
Section: Discussionmentioning
confidence: 99%